PENGARUH POLA ASUH ORANG TUA TERHADAP PENYALAHGUNAAN NARKOBA PADA REMAJA RAWAT JALAN DI PANTI REHABILITASI YAYASAN PENDAMPINGAN DAN PEMBERDAYAAN MASYARAKAT PAPUA JAYAPURA - Suriyani Suriyani (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
90% of Drug Users in Papua Among teenagers. The purpose of this study was to determine the effect of parenting style on drug abuse. The research design is a quantitative study with a cross-sectional design. The population in this study were adolescents aged 12-21 who were willing to become respondents and were recorded as outpatients at the Community Assistance and Empowerment Foundation as many as 113 adolescents from stage I totaling 59 adolescents from June - August and Phase II totaling 54 adolescents from September - November 2020. The sampling technique is simple random sampling. The number of samples is 30 respondents. Bivariate analysis test was made with Kendall's Tau. a total of 30 respondents, 17 (56.7%) parenting styles were good, while parenting styles were not good, 13 (43.3%) respondents. For drug abuse in the category of addicts there were 20 (66.7%) respondents while non-addicts (trying using drugs) were 10 (33.3%) respondents. Bivariate analysis, from a total of 17 respondents with good parenting patterns, drug abuse occurred in addicts as many as 17 (56.7%) respondents and non-addicts as much as 0% or none at all. Meanwhile, out of a total of 13 respondents with bad parenting styles, only 3 (10%) were addicts and 10 (33.3%) were not addicts. 20 (66.7%) respondents. From the results of Kendall's tau B test, a P-value of 0.000 (<0.005) is obtained, which means that Ha is accepted or there is an influence of parenting styles on drug abuse in adolescents. Suggestions that it is necessary to socialize good parenting patterns in order to reduce drug abuse.